2015
DOI: 10.1007/s13402-015-0246-4
|View full text |Cite
|
Sign up to set email alerts
|

Decreased CDK10 expression correlates with lymph node metastasis and predicts poor outcome in breast cancer patients - a short report

Abstract: Down-regulated CDK10 expression frequently occurs in breast cancers and correlates with disease progression and poor survival. CDK10 may serve as a prognostic biomarker for breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 31 publications
5
24
0
Order By: Relevance
“…It has been demonstrated that CDK10 expression is downregulated in nasopharyngeal carcinoma, and that overexpression of CDK10 strongly suppresses the growth and metastasis of cancer cells (10), which is consistent with studies on hepatocellular carcinoma and biliary tract cancer (11,12). More recent reports revealed that CDK10 expression levels were decreased in breast cancer, and that CDK10 expression was significantly associated with lymph node metastasis and unfavorable patient survival (13,14). These data indicated that CDK10 may serve as a tumor suppressor and that silencing of CDK10 may contribute to metastatic progression; however, the precise underlying molecular mechanism is largely unknown.…”
Section: Introductionsupporting
confidence: 82%
“…It has been demonstrated that CDK10 expression is downregulated in nasopharyngeal carcinoma, and that overexpression of CDK10 strongly suppresses the growth and metastasis of cancer cells (10), which is consistent with studies on hepatocellular carcinoma and biliary tract cancer (11,12). More recent reports revealed that CDK10 expression levels were decreased in breast cancer, and that CDK10 expression was significantly associated with lymph node metastasis and unfavorable patient survival (13,14). These data indicated that CDK10 may serve as a tumor suppressor and that silencing of CDK10 may contribute to metastatic progression; however, the precise underlying molecular mechanism is largely unknown.…”
Section: Introductionsupporting
confidence: 82%
“…Although a recent study argued that CDK10 is a candidate therapeutic target for colorectal adenocarcinomas (Weiswald et al, 2017), a number of reports indicate that CDK10 acts as a tumor suppressor in various cancers of the digestive system, including biliary tract cancer , hepatocellular carcinomas , gastric carcinomas (Zhao et al, 2017;You et al, 2018), and in nasopharyngeal carcinomas (You et al, 2013), gliomas (Li et al, 2018) and advanced breast cancers (You et al, 2015). These contradictory findings could be explained by the fact that ETS2, whose stability is controlled in part by CDK10/CycM phosphorylation (Guen et al, 2013), can function either as an oncogene or a tumor suppressor depending on various factors such as cellular context and p53 status (Martinez, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis. This procedure was performed as described previously (18)(19)(20)(21). Frozen tissue samples, including gastric cancer tissues and paired adjacent non-cancerous tissues obtained from 12 patients were prepared in radioimmunoprecipitation assay lysis buffer (Beyotime Institute of Biotechnology).…”
Section: Patient Information and Tissue Specimens A Microarray Chip mentioning
confidence: 99%
“…Immunohistochemical analysis was performed as described previously (20,21). Sections (4 µm thick) were cut from tissue specimens fixed in 10% buffered formalin and embedded in paraffin.…”
Section: Immunohistochemistry and Evaluationmentioning
confidence: 99%